Growth rates and scales of sand banks in the Colorado River Delta - N Carbajal; Y Montaño (Ciencias Marinas, 1999)
A linear stability analysis was carried out to investigate the sand bank formation in the Colorado River Delta. A truncated solution of the vorticity equation was included in the bottom evolution equation in order to evaluate the initial growth rates of the sand banks. The growth rates were estimated on the wave number plane for the hydrodynamic conditions of the Colorado River Delta, specifically for tidal ellipses, including unidirectional tides, and also for several depths. The wave lengths predicted with the model fluctuated between 2 and 7 km. These results agree quite well with the sand bank scales reported in the literature on the Colorado River Delta. The order of magnitude of the growth rates calculated in this study coincides with results obtained for the North Sea.